2021
DOI: 10.1111/ajr.12707
|View full text |Cite
|
Sign up to set email alerts
|

Critically reviewing the policies used by colleges to select doctors for specialty training: A kink in the rural pathway

Abstract: Objective To review the selection policies and models used by speciality colleges to select candidates for entry to vocational training, exploring whether these processes are rural‐focused. Design A systematic desktop audit of college selection processes and criteria was done via college websites (Australian Medical Council (AMC) requires selection information to be publicly available). Setting and main outcomes Material was extracted into a structured template, in 2020. Information extracted related to (i) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Only three studies were identified in the review that specifically discussed aspects of workforce education and training for future rural and remote practise [ 3 , 85 , 86 ] ( Table 6 ). Firstly, the Australia Future Workforce Report provided insight into the potential future ophthalmology workforce by reporting on the characteristics of 325 hospital non-specialists with the intention of undertaking vocational ophthalmology training [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only three studies were identified in the review that specifically discussed aspects of workforce education and training for future rural and remote practise [ 3 , 85 , 86 ] ( Table 6 ). Firstly, the Australia Future Workforce Report provided insight into the potential future ophthalmology workforce by reporting on the characteristics of 325 hospital non-specialists with the intention of undertaking vocational ophthalmology training [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…The perception that some training sites are less desirable than others is not unique to BPT and has been implicated in rural specialist workforce shortages. 1,21 Because basic physician trainees may complete AT and work as a consultant in the same region they are trained in, BPT selection decisions may influence the distribution of the physician workforce, and more centralised policy oversight may be warranted. Finally, differing selection practices may reflect conflicting DPE opinions about what makes an 'ideal' BPT recruit.…”
Section: Discussionmentioning
confidence: 99%
“…12 Selection into BPT follows a local, employer-led model. 1 While the RACP has published selection guidelines, 5 it is not directly involved in the recruitment or appointment of candidates, which is the responsibility of training sites and DPEs. 13 There is no standardised method of selection into BPT and little publicly available data on current practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides new evidence of the association between rural training time after leaving medical school and subsequent rural practice, after accounting for the contribution of the other key factors of childhood background and medical school rural training time across the These results suggest that the training period shortly following medical school plays a substantial role in shaping the subsequent distribution of the medical workforce, for both GPs and other specialists. This finding is concerning given that many studies have identified barriers faced by junior doctors seeking specialty college entry that may be magnified (or perceived that way) when based outside of metropolitan locations [34][35][36][37]. Examples of this include poor recognition of rural training experience in specialty college selection criteria, experiences of stigmatisation relating to rural medicine, reduced access to research opportunities in rural areas, access to smaller networks of reputable consultants within their target specialty, as well as simply having fewer visible local pathways [15,38,39].…”
Section: Discussionmentioning
confidence: 99%